A Destination VAT for CIS Trade - Perry, Victoria (IMF Working Papers; Working Paper, 1996)
In all of the new countries formed after the dissolution of the Soviet Union, other than the Baltics, the value-added taxes (VATs) adopted were 'hybrid' VATs that treat CIS trade differently from trade with the rest of the world. This paper inquires whether this is appropriate. The paper concludes that it would be better if all CIS countries applied the destination principle to CIS trade as well as to trade with the rest of the world. The paper addresses the economic, administrative and revenue allocation considerations underlying this decision.